Multiscale Determinants Drive Parasitization of Drosophilidae by Hymenopteran Parasitoids in Agricultural Landscapes - Valeria Trivellone; Michela Meier; Corrado Cara; Lucia Pollini Paltrinieri; Felix Gugerli; Marco Moretti; Sarah Wolf; Jana Collatz (Insects, 2020)
(1) The management of agricultural landscapes for pest suppression requires a thorough understanding of multiple determinants controlling their presence. We investigated the ecological preferences of indigenous parasitoids and their drosophilid hosts to understand the role of native parasitoids as biological control agents of the invasive frugivorous Drosophila suzukii. (2) Using data from an extensive field survey across different habitat types we analyzed the influence of abiotic and biotic factors on parasitoid and drosophilid communities at multiscale levels. (3) Eight parasitoid and 27 drosophilid species were identified. Thirty-four percent variation in drosophilid communities was explained by factors at the landscape scale, and 52% of significant variation of parasitoids by local distribution of three drosophilid species, mainly collected in woodland. Parasitoid communities were significantly influenced by microhabitat type (ground versus canopy) rather than habitat type. All parasitoids except Pachycrepoideus vindemmiae preferred the ground microhabitat. All parasitoids, with the exception of Trichopria drosophilae and Spalangia erythromera, displayed significant preferences among the drosophilid species used in the baited traps. (4) Since they can tolerate a broad range of habitat factors, altogether pupal parasitoids investigated in this study could play a role in biological control programs to suppress D. suzukii, but non-target effects have to be regarded.